2018
DOI: 10.1111/hel.12501
|View full text |Cite
|
Sign up to set email alerts
|

Diminished circulating concentration of interleukin‐35 in Helicobacter pylori‐infected patients with peptic ulcer: Its association with FOXP3 gene polymorphism, bacterial virulence factor CagA, and gender of patients

Abstract: Decreased IL-35 levels could be involved in PU development in H. pylori-infected individuals. IL-35 levels are affected by CagA status of H. pylori, participants gender, and genetic variations at rs3761548. The AA genotype and A allele at rs3761548 could represent a risk factor for PU development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(124 reference statements)
1
2
0
Order By: Relevance
“…It seems logical that IL-35 acts as a part of post-CPB anti-inflammatory phase and represents an attempt of the host to counteract the postoperative inflammatory responses, characterized by IL-1, IL-6, TNF [ 24 , 25 ] , and chemokines release, and of inflammatory cells, specially neutrophils activation [ 24 , 26 ] and the subsequent microcirculation and organ dysfunction [ 27 ] . Regarding this, we did not find any association between rs3761548, rs3761547 FoxP3 promoter polymorphisms and the IL-35 serum levels increase after CPB, but our findings about the association between IL-35 levels and preoperative (age, BMI) and intraoperative (CPB time and MAP) variables in carriers of the rs3761548 AA genotype are somehow consistent with Bassagh et al [ 28 ] study in peptic ulcer patients, Jafarzadeh et al [ 29 ] study in multiple sclerosis, and Chatrabnous et al [ 30 ] study in prostate cancer patients which showed that the IL-35 levels were significantly different in subjects with AA genotype.…”
Section: Discussionsupporting
confidence: 91%
“…It seems logical that IL-35 acts as a part of post-CPB anti-inflammatory phase and represents an attempt of the host to counteract the postoperative inflammatory responses, characterized by IL-1, IL-6, TNF [ 24 , 25 ] , and chemokines release, and of inflammatory cells, specially neutrophils activation [ 24 , 26 ] and the subsequent microcirculation and organ dysfunction [ 27 ] . Regarding this, we did not find any association between rs3761548, rs3761547 FoxP3 promoter polymorphisms and the IL-35 serum levels increase after CPB, but our findings about the association between IL-35 levels and preoperative (age, BMI) and intraoperative (CPB time and MAP) variables in carriers of the rs3761548 AA genotype are somehow consistent with Bassagh et al [ 28 ] study in peptic ulcer patients, Jafarzadeh et al [ 29 ] study in multiple sclerosis, and Chatrabnous et al [ 30 ] study in prostate cancer patients which showed that the IL-35 levels were significantly different in subjects with AA genotype.…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, diminished IL-35 is primarily associated with chronic infection [41] and type 1 diabetes mellitus [42]. Also, a low concentration of IL-35 was influenced in the progression of peptic ulcer of patients infected with H. pylori [43]. However, IL-35-mediated downregulation is effective to inhibit developed β-cell autoimmunity and encourage the use of IL-35 in T1DM treatment and other T-cell-mediated autoimmune diseases [44].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the following polymorphisms in various cytokines have been linked with an increased risk of PUD: TNF-a À1031 and À863 single nucleotide polymorphisms (SNPs) [11], low levels of interleukin-35 and interleukin-33,high levels of interleukin-37 with genetic variation at SNP rs3761548 (AA genotype and A allele) in the forkhead box p3 (FOXP3) gene, rs1929992 (GG genotype and G allele) in the intron 3 region of the IL-33 gene, and the rs3811047 and rs2723176 SNPs (genotype GG and allele G, genotypes CC and allele C, respectively) on chromosome 2q13 respectively with CagA-positive HP infection [12][13][14]. In these studies, certain limitations in the expression of a genetic region, determinations of regulatory T (Treg) cell frequency and the measurements of other cytokines were not investigated.…”
Section: Introductionmentioning
confidence: 99%